El presupuesto referencial como un elemento esencial para afrontar la crisis económica del Ecuador en las compras públicas (Tema Central) - Díaz Colmachi, Juan Francisco (2016)
Ecuador is facing an economic crisis caused by external factors affecting directly to public purchases. However the government is trying to minimize the situation, the day by day of the department of public acquiring is starting to be incompatible with the talks in platform. The referential budget selected for each employing process, is the primary point to precaution, to procure that the crisis effects will not affect directly to the public acquisitions and to be able to satisfy the citizens needs with less resources. How can we get this solved? First evaluating the components that incorporates the referential budget, tools that motivates the public employee to manage referential budgets that are adjusted to actuality, creating innovative procedures to follow close the public expenses and to be able to be conscious that the public expense for 2016 will be lower.